Integrated Cumulative Grade Point Average (iCGPA) Benefits and Challenges of Implementation for the Medical Faculty - Suhaila Sanip; Nur Faraheen Abdul Rahman (Penerbit USM, 2024)
Education in Medicine Journal, 2018;10(1):69-80.